2020
DOI: 10.21303/2613-5647.2020.001296
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of the Economic Situation on the Socio-Economic Development in the European Union Countries by Means of the Modified Hdi Index

Abstract: The aim of the research is an analysis of the influence of the economic indicators on the socio-economic development of EU countries. The synthetic measure of socio-economic development is calculated by means of the following determinants: ‘Economy and Finance’, ‘Science and Technology’, ‘Health’, ‘Education’ and ‘Living Conditions’. This index of the socio-economic development of residents of the European Union countries has been created as an arithmetic mean of indicators, counted for particular determinants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…Meanwhile, Kubu Raya Regency negatively influenced the Human Development Index (HDI) in West Kalimantan Province. [1], [7] Y = -203.6528 + (-2.510601) POVit + 6.234375 PEit + 0.086995 UEit + 8.600384 GRDPit + e Then, the results of the research regression estimation on the determinants of the quality of human resources in West Kalimantan Province showed that all the independent variables in this study, including poverty (POV), per capita expenditure (PE), unemployment (UE), and gross regional domestic product (GRDP), revealed significant results for increasing the development index (HDI) in West Kalimantan Province. The highest value was in the gross regional domestic product (GRDP) variable, amounting to 8.600384.…”
Section: Results Analysis and Discussionmentioning
confidence: 99%
“…Meanwhile, Kubu Raya Regency negatively influenced the Human Development Index (HDI) in West Kalimantan Province. [1], [7] Y = -203.6528 + (-2.510601) POVit + 6.234375 PEit + 0.086995 UEit + 8.600384 GRDPit + e Then, the results of the research regression estimation on the determinants of the quality of human resources in West Kalimantan Province showed that all the independent variables in this study, including poverty (POV), per capita expenditure (PE), unemployment (UE), and gross regional domestic product (GRDP), revealed significant results for increasing the development index (HDI) in West Kalimantan Province. The highest value was in the gross regional domestic product (GRDP) variable, amounting to 8.600384.…”
Section: Results Analysis and Discussionmentioning
confidence: 99%
“…Another issue that should be noted is the fact that EU governments should allocate more resources to health protection and improving the living conditions of the inhabitants of the European Union countries [Migała-Warchoł & Sobolewski, 2020). In further studies which aim will be the analysis of the results of the third wave caused by the SARS-CoV-2 virus is planned to use the SIR model.…”
Section: Discussionmentioning
confidence: 99%
“…Socio-economic governance policies encompass various measures and interventions used by governments, institutions and organizations to manage and regulate economic activities and social well-being. This study specifically focuses on the fiscal aspect of socio-economic governance, which is measured through investments in education, health and R&D. The importance of investment in human development as a measure of socio-economic governance is also highlighted in the study by Migała-Warchoł (2019).…”
Section: Literature Reviewmentioning
confidence: 99%